2023
DOI: 10.21037/tau-23-32
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of germline mutations in cancer susceptibility genes in Chinese patients with renal cell carcinoma

Abstract: Background: Germline pathogenic variants are estimated to affect 3-5% of patients with renal cell carcinoma (RCC). The identification of patients with hereditary RCC is important for cancer screening and treatment guidance.Methods: Whole-exome sequencing (WES) (n=69) or gene panel sequencing containing 139 genes (n=54) related to germline cancer predisposition was used to analyze germline mutations in 123 patients with

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 75 publications
2
9
0
Order By: Relevance
“…The data on low population incidence and RCCspecific penetrance [127] are in apparent conflict with the results of a multigene sequencing study, which revealed FH pathogenic or likely pathogenic variants in 7/254 (2.8%) RCC patients [9]. There are several other reports suggesting that germline FH gene alterations make a noticeable contribution to RCC morbidity [8,12,14,23,130].…”
Section: Fumarate Hydratase Tumor Predisposition Syndrome (Fhtps)mentioning
confidence: 82%
See 4 more Smart Citations
“…The data on low population incidence and RCCspecific penetrance [127] are in apparent conflict with the results of a multigene sequencing study, which revealed FH pathogenic or likely pathogenic variants in 7/254 (2.8%) RCC patients [9]. There are several other reports suggesting that germline FH gene alterations make a noticeable contribution to RCC morbidity [8,12,14,23,130].…”
Section: Fumarate Hydratase Tumor Predisposition Syndrome (Fhtps)mentioning
confidence: 82%
“…PPGLs: 1:51,667-1:77,500 (Denmark) [27] N/A 0.7-0.9%: 0.8% [9]; 0.7% [11]; 0.8% [14]; 0.9% [8,12] PPGLs: 20-43% [17,18,28] PPGLs: SDHB: 21.8%; SDHD: 43.2%; SDHC: 25% [29] SDHA: clinical series: 10-30%; population-based estimates: 0.1-4.9% [30] SDHx-associated RCCs: SDHB: 4.2%; SDHD, SDHC, SDHA: the increased risk has not been proven [29] Rarely: thyroid carcinomas, GIST, pituitary adenomas, etc.…”
Section: Prevalence Of Sdhx-associatedmentioning
confidence: 99%
See 3 more Smart Citations